Zeke Meeks vs. the gruesome girls - Green, D. L. (Debra L.) (Zeke Meeks, 2012)
Third-grader Zeke Meeks already has two sisters, so he is bitterly disappointed when his new neighbor proves to be a girl--can Charlie change his mind and prove to him that boys and girls can play together?